STUDI TENTANG POSISI KKN-PPL DALAM DINAMlKA PERKEMBANGAN PERGURUAN TINGGI DAN TUNTUTAN MASYARAKAT - Sukardi Sukardi (Jurnal Cakrawala Pendidikan, 2007)
This article concerns a reposItIOn study on the KKN-PPLprogram conducted in the developmentof a dynamic university inrelation to community needs, which had three important objectives,(1) to gain information of the effectiveness of the KKN-PPLprogram in relation to the university curriculum implementation, (2)to gain informationof resistance occurring during theimplementation of the KKN-PPL integrated program, and (3) todescribe stakeholders' perceptions of information about the KKNPPL program hosted by the State Universityof Yogyakarta.The study was a policy research, in which several factorssupporting or resisting an effective implementation of the KKN-PPLwere analyzed and described intensively by using a descriptiveexploratory method to discover patternsof theory based on a set ofdata scores.The study on the repositioning of the KKN-PPL program in thedevelopmentof a dynamic university in relation to community needsproduces three important recommendations. Firstly, it is possiblethat the KKN-PPL program is to be conducted separatelyin order toobtain its specific objectives, the KKN program, essentially aprogram to make students learn from experiencein doing publicservice for the community, to be specifically for students with nonteacher majors and PPL, essentially a programof field teachingpractice, to be for students majoring in teaching. The management ofthe KKN program used to be essentially by LPM, a public serviceinstitution in the university, and the administration ofPPL used to beessentially by UPPL, a university unit managing students' field teaching practice. Therefore, secondly, the manager of the KKNprogram and thatof the program of PPL is to be returned to itsformer function. This recommendation is alignedto a historicalaspectof conducting the KKN program within a three-monthduration on location. Thirdly, alternatively, the integrated KKN-PPLprogram isto be continually handled at UNY by enhancing itsmechanism system into a more efficient and effective one.